Molecular cloning of human CREB-2: an ATF/CREB transcription factor that can negatively regulate transcription from the cAMP response element. - Karpinski, B A (1992)
The cAMP response element (CRE) is an octanucleotide motif (TGACGTCA) that mediates diverse transcriptional regulatory effects. In this report we describe the isolation and characterization of a full-length cDNA that encodes a CRE binding protein called CREB-2. Like other ATF/CREB transcription factors, the 351-amino acid CREB-2 protein contains a COOH-terminal leucine-zipper motif and an adjacent basic domain. CREB-2 mRNA is expressed ubiquitously in human tumor cell lines and mouse organs suggesting that it is involved in regulating transcription in a wide variety of cell types. Overexpression of CREB-2 resulted in a consistent and significant repression of CRE-dependent transcription in CV-1 cells. Deletional analyses localized the transcriptional repressor activity of CREB-2 to a 102-amino acid COOH-terminal region (amino acids 249-351) that contains the leucine-zipper and basic domains of the molecule. These results demonstrate that CRE-dependent transcription can be both positively and negatively regulated by structurally related members of the ATF/CREB family.